Model of transformational leadership style and organizational culture to increase employee performance in the logistics services industry - Sirajuddin, Sirajuddin; Santoso, Ahmad Bardzuki; Katili, Putiri Bhuana; Gunawan, Akbar (Journal Industrial Servicess, 2024)
The rapid growth of the logistics industry has impacted competition between companies, and human resource planning is a critical factor in achieving company goals. A company's success can be determined based on the performance of its human resources. Several factors influence employee performance, including transformational leadership style, organizational culture, and work motivation. Improving employee performance to enhance success and productivity is a challenging task for every company. The purpose of this study is to examine the influence of transformational leadership style and organizational culture on employee performance, with work motivation as an intervening variable. The research method used is quantitative, with variables measured using a Likert scale. This research involved a sample of 64 employees from a logistic company. Data collection techniques included interviews and questionnaires. The data analysis was conducted using Partial Least Squares - Structural Equation Modeling (PLS-SEM) with Smart-PLS version 4. The results of this study show that transformational leadership style and organizational culture have a positive and significant effect on work motivation and employee performance. However, work motivation has a negative and insignificant effect on employee performance. Furthermore, transformational leadership style has a negative and insignificant effect on employee performance through work motivation as an intervening variable, and organizational culture has a negative and insignificant effect on employee performance through work motivation as an intervening variable.